2014
DOI: 10.1139/cgj-2012-0476
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale analysis of cone penetration test (CPT) in a virtual calibration chamber

Abstract: A virtual calibration chamber was developed using a three-dimensional (3D) discrete element method (DEM) to perform cone penetration tests (CPTs) on a discrete analogue of Ticino sand. The macroscale response of the DEM model was previously shown to be in good quantitative agreement with that of analogous physical models. In the current study the performance of the model at meso and microscale levels of resolution is examined. The microscale response is examined using particle displacements and contact force d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 33 publications
3
52
2
6
Order By: Relevance
“…For example, Jiang et al (2008) suggested that the failure mechanisms taking place during cone penetration were derived from a combination of four motions of the grains from the cone. Similar studies using DEM have also been presented by Kilonch and O'Sullivan (2007) and Butlanska et al (2014). 4 …”
Section: Cone Penetration At the Microscalesupporting
confidence: 79%
“…For example, Jiang et al (2008) suggested that the failure mechanisms taking place during cone penetration were derived from a combination of four motions of the grains from the cone. Similar studies using DEM have also been presented by Kilonch and O'Sullivan (2007) and Butlanska et al (2014). 4 …”
Section: Cone Penetration At the Microscalesupporting
confidence: 79%
“…A further step along this line is to use upscaled particle sizes, a technique previously applied in geotechnical engineering applications (Utili & Nova, 2008;Gabrieli et al, 2009;Arroyo et al, 2011;Butlanska et al, 2013). Upscaling rules are here proposed for particle strength and for contact stiffness parameters, using both linear and Hertzian contact laws.…”
Section: Introductionmentioning
confidence: 99%
“…Liyanapathirana [9] and Tolooiyan and Gavin [10] adopted the arbitrary Lagrangian Eulerian (ALE) method to preserve the quality of the mesh during the cone's penetration. However, all of these FE-based methods lack the ability to describe the post-failure phenomena that are associated with the severe grain rearrangement, sliding, rolling and crushing [11].…”
Section: Introductionmentioning
confidence: 99%